Specific Barriers for Quadruple Helix Innovation Model Development – Case of Croatia (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2016)
There has been a lot of theoretical discussion about triple helix and quadruple helix methodologies for innovation and knowledge transfer in the context of local development and even smart cities. The goal of this paper is to describe specific barriers related to ICT uptake, usage and development related to knowledge based capital and their role in Croatia, especially in the context of passing from triple helix (academia, business, government) to quadruple helix (academia, business, government, NGOs/citizens) model. Specific barriers exist in each country, and they may be divided into technological, organisational, human, societal and/or cultural barriers. The case of Croatia is specifically analysed and compared to other countries in the region and in the EU. The lack of participative culture and other criteria influencing social dynamics are particularly addressed in order to reach a conclusion about country specific barriers and provide policy advice for decision makers.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.